Analisis Pengaruh Beban Terhadap Efisiensi Generator Unit 2 PLTP PT. Indonesia Power UPJP Kamojang - Muharrir Muharrir; Ibnu Hajar (KILAT, 2019)
Geothermal as a newest natural resource for Indonesian. PLTP PT. Indonesia Power as one of subsidiaries of PLN that is focused on generating using geothermal resource. One of the important components in the system of PLTP is a generator. PLTP Kamojang had been operating for about ±30 years, where there are still some problems that will reduce the efficiency of generator. The generator at PLTP Kamojang unit 2 must be operated more than 90% so that it will be able to supply electric power for 150kV. If the generator operated with the efficiency under 80%, so the supply of energy will not be maximum, because there are so much energy of electric lost caused by the losses in the generator. That is why needs to be analyzed toward the efficiency of the generator, whether the generator still works optimum or not. The result of analyses from the month of February 2019 as long as 1 month, found that the efficiency of generator unit 2 is about 92,888%. If comparing by the efficiency of generator as design as much as 98,4%. The efficiency value of the generator unit 2 Kamojang is decreased for about 5,51%. This condition showed that the generator still reliable one in supllying electric power.